An Introduction to the climate-smart agriculture papers - Rosenstock, Todd S.; Rohrbach, David; Nowak, Andreea C.; Girvetz, Evan Hartunian (Springer, 2019)
Over the last decade, international concerns about climate change have stimulated broad investment in the pursuit of agriculture that is more climate-smart. These concerns are particularly pressing in Africa, where most farmers remain severely impoverished and dependent on rain-fed production systems. This volume collates some of the latest research from agricultural scientists working to speed up the development and adoption of more climate-smart farming systems in eastern and southern Africa. These 25 papers highlight ongoing efforts to better characterise climate risks, develop and disseminate climate-smart varieties and farm management practices, and integrate these technologies into well-functioning value chains. The papers emphasise the additional research efforts needed to improve the understanding and response to climate risk. The expert authors also make suggestions for strengthening the responsiveness of agricultural research and extension systems to future climate changes.